Association of Polymorphisms at the SIX1/SIX6 Locus With Normal Tension Glaucoma in a Korean Population. Issue 9 (3rd September 2022) - Shin, Hye-Young; Lee, Young Chun; Lee, Mee Yon
Abstract : Précis: We demonstrated that SIX1/SIX6 locus polymorphism (rs10483727 and rs33912345) was significantly associated with a genetic susceptibility to NTG in a Korean population. More studies are needed to investigate whether the SIX1/SIX6 locus is associated with NTG among various ethnic populations. Purpose: Several previous studies have reported that the relevance of the SIX1/SIX6 locus to open angle glaucoma (OAG) in various ethnic populations. However, definitions of OAG patients were different among those studies. The relevance of the SIX1/SIX6 locus to normal tension glaucoma (NTG) in a Korean population remains uncertain. Therefore, the purpose of this study was to investigate the relationship of the SIX1/SIX6 locus with NTG in a Korean cohort. Method: Patients with NTG and ethnically matched healthy controls were recruited from eye clinics in Korea (210 cases and 117 controls). Four polymorphisms (rs33912345, rs12436579, rs2179970, and rs10483727) of the SIX1/SIX6 locus were genotyped for 327 subjects using a TaqMan single nucleotide polymorphism genotyping assay. Results: The rs33912345 polymorphism was significantly correlated with NTG in the recessive model [odds ratio (OR): 0.265; 95% confidence interval (CI): 0.078–0.898, P =0.033], but not in the allelic and dominant models (both P >0.05). The SNP rs10483727 was significantly associated with NTG in the allelic model (OR: 0.674; 95% CI: 0.464–0.979, P =0.038) and the recessive model (OR: 0.187; 95% CI: 0.058–0.602, P =0.005). Genetic association analysis of SNP rs12436579 and rs2179970 revealed no significant difference in genotype distribution between NTG cases and controls in the allelic, dominant, or recessive models (all P >0.05). Conclusion: The current study found that SIX1-SIX6 locus rs10483727 and rs33912345 polymorphisms were significantly associated with NTG risk in the Korean population.